2009 24th International Conference Image and Vision Computing New Zealand 2009
DOI: 10.1109/ivcnz.2009.5378361
|View full text |Cite
|
Sign up to set email alerts
|

Towards a generalized colour image segmentation for kiwifruit detection

Abstract: Abstract-Developing robust computer vision algorithms to detect fruit in trees is challenging due to less controllable conditions, including variation in illumination within an image as well as between image sets. There are two classes of techniques: local-feature-based techniques and shape-based techniques, which have been used extensively in this application domain. Out of the two classes, the local-feature-based techniques have shown higher accuracies over shape-based techniques, but are less desirable due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Image processing at orchards spans a large variety of fruits such as grapes (Nuske et al, 2014;Font et al, 2015), mangoes (Chhabra et al, 2012;, apples (Linker et al, 2012;Wang et al, 2013;Stajnko et al, 2009;Silwal et al, 2014;Ji et al, 2012;Kim et al, 2015;Hung et al, 2015), citrus (Li et al, 2011;Annamalai et al, 2004;Sengupta and Lee, 2014;Regunathan and Lee, 2005;Qiang et al, 2014), kiwifruit (Wijethunga et al, 2009) and peaches (Kurtulmus et al, 2014). Fruit classification is generally performed by transforming image regions into discriminative feature spaces and using a trained classifier to associate them to either fruit regions or background objects such as foliage, branches, ground etc.…”
Section: Related Workmentioning
confidence: 99%
“…Image processing at orchards spans a large variety of fruits such as grapes (Nuske et al, 2014;Font et al, 2015), mangoes (Chhabra et al, 2012;, apples (Linker et al, 2012;Wang et al, 2013;Stajnko et al, 2009;Silwal et al, 2014;Ji et al, 2012;Kim et al, 2015;Hung et al, 2015), citrus (Li et al, 2011;Annamalai et al, 2004;Sengupta and Lee, 2014;Regunathan and Lee, 2005;Qiang et al, 2014), kiwifruit (Wijethunga et al, 2009) and peaches (Kurtulmus et al, 2014). Fruit classification is generally performed by transforming image regions into discriminative feature spaces and using a trained classifier to associate them to either fruit regions or background objects such as foliage, branches, ground etc.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, learning methods are robust to dynamic conditions such as lighting, camera viewpoint, fruit occlusion and fruit size. Wijethunga et al [Wijethunga et al, 2009] used a Self-Organizing Map (SOM) model to detect kiwifruit. The normalised pixel data in L*a*b* colour space was used for training the model, and the author concluded that its performance was better compared to using the original dataalthough the author has not quantified the result.…”
Section: Related Workmentioning
confidence: 99%
“…Jimenez et al [A. R. Jiménez et al, 2000] suggested that using artificial lighting can reduce shadows caused by sunlight. Another suggestion, for having consistent lighting conditions, was capturing images at nighttime [Fu et al, 2015;Fu et al, 2017;Wijethunga et al, 2009;Wang et al, 2013] or on an overcast day [Dias et al, 2018].…”
Section: Related Workmentioning
confidence: 99%